THE ROLE OF PLAY IN THE MOTOR DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS (EARLY YEARS) (CIPEEX, 2025)
The text aims to explore the importance of play in child development, addressing its benefits for motor, cognitive, social, and emotional skills. Play, characterized as spontaneous, pleasurable, and healthy, plays a central role in children's motor development, especially in elementary school. Studies such as those by Friedmann, Rosado, and Vygotsky emphasize that playful activities are fundamental for physical, emotional, and intellectual development. Kishimoto (2017) highlights that play reveals children's personalities, providing freedom to express feelings and behaviors. Motor development, according to De Paiva (2015), is a sequential process influenced by biology, tasks, and the environment. At the beginning of schooling, children improve motor skills such as running, jumping, and balancing, which are part of their normal progress. The sociocultural context and access to play also influence this development. Freire (2007) emphasizes the need to develop motor skills considering their cognitive and social consequences. Research based on literature reviews indicates that play not only improves motor skills but also promotes the integral development of children, although inequalities in access to these activities limit the motor progress of some children.
Keywords: play; motor development; playfulness; elementary school; motor skills; sociocultural context; personality; children